Cardiovascular outcomes in high risk patients undergoing OPCAB surgery compared to Traditional CABG - Suwatri, Widya Trianita; Hanafy, Dudy Arman; Sugisman, Sugisman (Fakultas Kedokteran Universitas Brawijaya, 2021)
The benefit of coronary artery bypass graft (CABG) for coronary artery disease (CAD) with Ejection Fraction (EF) £30% and ischemic burden (IB) £10% is still debateable. The objective of this study is to analyze mortality and morbidity in patients with EF £30% and ischemic burden £10% undergoing OPCAB compared to traditional CABG (TCABG). The retrospective analytic cohort study was performed using data from January 2015–November 2018 at National Cardiovascular Center Harapan Kita Jakarta, Indonesia. 109 patients were included. 35 patients undergoing OPCAB and 74 patients undergoing TCABG. The primary outcomes were mortality rate, morbidity rate, and length of stay. Arrhytmia is statistically lower in OPCAB compared to TCABG (8.6% vs 39.2%; p = 0.001). Kidney injury is statistically lower in OPCAB (8.6% vs 27.0 %; p = 0.027). Stroke is statistically lower in OPCAB (1.0 % vs 17.6%; p = 0,032). There is no significant difference between OPCAB and TCABG in mortality, 5.7% vs 16.2%, (RR 3.20; CI 95% 0.67–15.12; p = 0.126). There was a statistically significant difference in the occurrence of postoperative morbidity in CAD patients with EF < 30% and IB < 10% who underwent OPCAB surgery compared with patients who underwent TCABG. Mortality that occurred after OPCAB procedure was lower in CAD patients with EF < 30% and IB < 10% compared to TCABG although the statistical difference was not significant. Therefore, patients with this condition are more adviseable to undergo OPCAB. Keyword: left ventricular dysnfunction, ischemic burden, off-pump coronary artery bypass grafting